Septology - Fosse, Jon, 1959- (Transit Books, 2022)
What makes us who we are? And why do we lead one life and not another? Asle, an aging painter and widower who lives alone on the southwest coast of Norway, is reminiscing about his life. His only friends are his neighbor, Åsleik, a traditional fisherman-farmer, and Beyer, a gallerist who lives in the city. There, in Bjørgvin, lives another Asle, also a painter but lonely and consumed by alcohol. Asle and Asle are doppelgängers--two versions of the same person, two versions of the same life, both grappling with existential questions about death, love, light and shadow, faith and hopelessness. The three volumes of Jon Fosse's Septology--The Other Name, I is Another, and A New Name--collected here for the first time, are a transcendent exploration of the human condition, and a radically other reading experience--incantatory, hypnotic, and utterly unique.